Hubungan Perhatian Orang Tua terhadap Keterampilan Membaca Anak di Kelas III SDN Gugus Pucang Harapan Kecamatan Mranggen Kabupaten Demak - Az Zahra, Anggun Ayu; Fathurrahman, Moh. (Universitas Muhammadiyah Magelang, 2026)
This study aims to analyze the relationship between parental attention and the reading skills of third-grade students at Gugus Pucang Harapan Elementary School, Mranggen District, Demak Regency. This study used a quantitative approach with a correlational approach. The study population was 163 students, with a sample of 116 students determined using simple random sampling based on the Slovin formula with a 5% margin of error. Data collection techniques included questionnaires, interviews, and documentation. The parental attention instrument consisted of 18 statements that were declared valid and reliable. Data analysis was performed using descriptive and inferential statistics using SPSS version 21, including normality tests, linearity tests, Pearson Product Moment correlation, and simple regression. The results showed that parental attention was in the fair category with an average score of 44.26, while students' reading skills were in the good category with an average score of 82.93. The correlation test showed a significance value of 0.000 (<0.05) with a correlation coefficient of 0.720, which is considered strong and positive. The coefficient of determination of 51.84% indicates that parental attention contributes 51.84% to students' reading skills, while the remainder is influenced by other factors. Thus, it can be concluded that there is a significant and positive relationship between parental attention and the reading skills of third-grade elementary school students.